A Simple Chemical Method for Synthesis of BaFe12O19 Hard Magnetic Nanoparticles. Issue 1 (2nd January 2016) - Nabiyouni, Gholamreza; Chegini Aliabadi, Parvin; Ghanbari, Davood; Julaee, Mahdie
Abstract : Hard magnetic BaFe12 O19 (BaFe) nanoparticles were synthesized via a facile chemical reaction between Ba(NO3 )2 and Fe(NO3 )3 . The effect of different parameters such as precursor, temperature and solvent on the morphology and particle size was investigated. Nanoparticles were characterized using X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Magnetic properties of the samples were also investigated using an alternating gradient force magnetometer. The barium ferrite nanoparticles exhibit ferrimagnetic behavior at room temperature, with a saturation magnetization of 46 emu/g and a coercivity of 3828 Oe.